2015
DOI: 10.1161/strokeaha.115.011031
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-12 Induces Blood–Brain Barrier Damage After Focal Cerebral Ischemia

Abstract: T he blood-brain barrier (BBB) is formed by the endothelial cells of cerebral microvessels, which are distinguished from peripheral endothelial cells by their lack of fenestrations, minimal pinocytotic activity, and the tight junctions (TJs).1 In addition to endothelial cells, the BBB is composed of pericytes, astrocytes, neurons, and extracellular matrix.2 Endothelial cells and pericytes are surrounded by the extracellular matrix, which is composed of structural proteins, such as collagen type-IV, laminin, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 34 publications
(47 reference statements)
3
64
0
Order By: Relevance
“…In agreement with these studies, our recent studies in a rat model of transient focal cerebral ischemia and reperfusion reported the post-ischemic induction of MMP-9 activity through gelatin zymography analysis [4,5]. TIMP-1 upregulation after stroke in the human infarcted brain tissue was recently reported [25].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In agreement with these studies, our recent studies in a rat model of transient focal cerebral ischemia and reperfusion reported the post-ischemic induction of MMP-9 activity through gelatin zymography analysis [4,5]. TIMP-1 upregulation after stroke in the human infarcted brain tissue was recently reported [25].…”
Section: Discussionsupporting
confidence: 71%
“…Manipulation of either MMP-9 or MMP-12 by neutralizing antibodies or siRNA-/shRNAmediated gene silencing attenuated the brain damage in rats after ischemic stroke [4][5][6][7][8]. HUCB-MSCs treatment in spinal cord injured rats prevented the dysregulation of various MMPs including MMP-9 and MMP-12 as well as improved their locomotor recovery [9,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order for the HUCB-MSCs to migrate to the ischemic brain after their administration, they should be permeable through the blood brain barrier (BBB). Recently, we reported the possible disruption of BBB, which occurred as early as two-hours post MCAO without reperfusion in the same rodent model of focal cerebral ischemia [14]. Therefore, it is quite possible for the HUCB-MSCs administered one hour after reperfusion subsequent to a two-hour ischemia, to reach various regions of the ischemic brain.…”
Section: Stem Cells Migrated To the Ischemic Brain After Administrationmentioning
confidence: 99%